Analysis of Product Development in SMEs “Monity Jaya Bersama” with The Analytical Hierarchy Process (AHP) Method - Andi Ridwan Makkulawu; Ilham Ahmad; Imran Muchtar; Widyiastuti Widyiastuti (Citakonsultindo, 2023)
The purpose of this research is to obtain a decision for the priority of the product to be developed SMEs with the AHP method. The method used in this study in determining the appropriate product to be developed for the products of SMEs Monity Jaya Bersama is the Analytical Hierarchy Process (AHP). AHP is used to determine the weight of the 4 criteria, namely taste, price, quality and packaging. Meanwhile, alternative product rankings from UKM are original flavor, mocha flavor and extra spicy flavor. Respondents in the AHP method are determined based on the criteria of expertise and involvement in product development activities, from the results of data processing the weights generated from each criterion are Taste 0.30%, Price 0.10%, Quality 0.40% and packaging 0.19%. The conclusion of this study is quality is the first rank following taste, price and quality.